IL-17 upregulates MCP-1 expression via Act1 / TRAF6 / TAK1 in experimental autoimmune myocarditis. (April 2022) - Huang, Xiao; Li, Zhuolun; Shen, Xinhe; Nie, Na; Shen, Yan
Highlights: IL-17 could upregulate the expression of MCP-1 in experimental autoimmune myocarditis. The mechanism of IL-17 regulation for MCP-1 is dependent on the activation of Act1/TRAF6/TAK1 signaling pathway. Blocking Act1/TRAF6/TAK1 could attenuate inflammatory cell infiltration during experimental autoimmune myocarditis. Abstract: Myocarditis is a kind of myocardial inflammatory infiltration disease. Many interventions are not effective in the treatment of myocarditis because the mechanism of myocarditis has not been elucidated. Previous studies have found that interleukin-17 (IL-17) could stimulate the expression of monocyte chemokine protein 1 (MCP-1) and mediate myocardial inflammatory infiltration. This study aimed to explore the role of Act1/TRAF6/TAK1 cascade in IL-17-induced MCP-1 expression based on a well-designed experimental autoimmune myocarditis (EAM) model. It was found that IL-17 could stimulate the expression of MCP-1 by activating Act1/TRAF6/TAK1 cascade in EAM. The expression of Act1, TRAF6 and TAK1 followed downregulation by the application of IL-17 antibody. Additionally, myocardial inflammatory cell infiltration was observably alleviated by interfering TAK1 with TAK1 siRNA, and both MCP-1 mRNA and protein expression followed downregulation. This study suggested that IL-17 could activate the Act1/TRAF6/TAK1 pathway to upregulate MCP-1 expression in the EAM, and will offer a new perspective for the study on the mechanism of myocarditis.